Constructing minzu: the representation of minzu and Zhonghua Minzu in Chinese elementary textbooks. Issue 6 (2nd November 2018) - Chu, Yiting
ABSTRACT: This article examines the role of school textbooks on nation-building in China by examining how the Chinese concepts of minzu and Zhonghua Minzu are constructed in elementary language and social studies textbooks. This study draws on the relationships between ideology and school curriculum as its theoretical framework and adopts a combination of content analysis and critical discourse analysis to critically examine content about minzu in these textbooks. The findings of this study reveal the ambiguous meanings of the word minzu in the examined textbooks and the process through which its semantic ambiguity is contributing to the discursive construction of the Zhonghua Minzu ideology, which is important for China to position itself as a unified, multiethnic country. The use of metaphoric languages and strategic rendering of two key narratives, humiliation and civilization in Chinese history, also help to solidify the Zhonghua Minzu identity.